An experimental Investigation of stagnant air pollution dispersion around a building in a turbulent flow. (October 2022) - Keshavarzian, Erfan; Kwok, Kenny C.S.; Dong, Kejun; Chauhan, Kapil; Zhang, Yu
Abstract: This paper investigates air pollution dispersion and exposure time around a building in a turbulent flow via tracer gas techniques. In the wind tunnel experiments, the tracer gas as the air pollutant model was trapped around the building model and exposed to a boundary layer wind flow. First, flow visualisation was performed, illustrating the highly transient features of wind flow and air pollution dispersion process dominated by underlying wind-structure interaction mechanisms. Next, the concentration field was normalised, analysed and presented as a function of time around the building. Evidently, the stagnant air pollution shields from the wind flow in the building's wake, causing a much longer air pollutant exposure time compared to the regions near the windward and side faces. The air pollutant exposure time in the side region was longer than in the windward region, influenced by the separation-reattachment and bifurcating flow near the side and windward faces, respectively. These results are compiled in order to provide a validation database for similar CFD studies on exposure time. Also, the normalised air pollutant exposure time was scaled up and integrated with air pollutant concentration in the form of two new indices to establish a methodology for the interpretation of air pollutant exposure time in full-scale built-environment scenarios. Highlights: Novel experiments performed on air pollutant exposure time around a building model. Flow visualisation shows the transient features of flow and pollution dispersion. Air pollutant exposure time in the windward, leeward and side regions were measured. Relationship of air pollutant exposure time at different scales was established. Two new indices, APEX and te, are proposed for evaluating air pollution dispersion.